Study to assess the status of bupivacaine hydrochloride in the management of essential trigeminal neuralgia (Bangladesh Journal of Physiology and Pharmacology, 2014)
Trigeminal neuralgia (TN) is a rare form of neuropathic facial pain characterized by severe paroxysmal pain in the face. The treatment of trigeminal neuropathic pain disorder is a major therapeutic challenge. Medical therapy often fails either due to poor responses to drugs or to unacceptable side effects and for those cases local anesthesia should be considered. Twenty patients (nine men and eleven women) who were diagnosed with TN previously and were not responsive to further medical treatment were selected for treatment. For this study, the affected nerve was blocked with 1.5 ml of 0.5% bupivacaine HCl. Patients visual analogue scores (VAS) were recorded on preoperative day and on post operative at day 3, 7days, 15 days. There was a significant difference between mean preoperative and postoperative VAS value. Preoperative value was 83.10± 6.06, at postoperative 3 days was 39.60 ± 7.86, at postoperative 7 days was 16.25 ± 6.46 and at postoperative 15 days was 3.30 ± 3.19. So it can be concluded that administration of 1.5 ml of 0.5% bupivacaine HCl nerve block at regular interval can be used as treatment for patients who are affected by the side effects from high-dose antiepileptic drugs. http://dx.doi.org/10.3329/bjpp.v26i1-2.19965 Bangladesh J Physiol Pharmacol 2010; 26(1&2) : 30-33